Decoherence of quantum superpositions in relativistic settings - Batista, Levy Bruno do Nascimento [UNESP] (Universidade Estadual Paulista (UNESP), 2025)
Recently, Danielson, Satishchandran, and Wald have proposed a novel source of decoherence of charges and masses in a spatial superposition state when placed in a spacetime with Killing horizons. They argued that the effect is primarily caused by the emission of soft particles through these horizons, which will eventually occur even if the process is assumed to be adiabatic. It turns out this decoherence is intimately related to the presence of low-frequency quanta in the thermal radiation, as described by stationary observers in the Schwarzschild and Rindler spaces, which arises depending on the choice of vacuum state. We investigate this claim in a rather different setting, with a gapless detector interacting with a massive scalar field. We introduce how such interaction is described and how to quantify the resulting decoherence. Then, we investigate our proposed model in two seminal cases: We consider that the components of the spatial superposition are inertial and that they are uniformly accelerating in the Minkowski space. We highlight the similarities and differences between our results and those of previous studies when the system is tuned in an analogous regime. Finally, we discuss what we sought to improve with our model and how it might clarify some questions left open in the original work.

centemente, Danielson, Satishchandran e Wald propuseram uma nova forma de decoerência de cargas e massas em um estado de superposição espacial quando colocadas em um espaço-tempo com horizontes de Killing. Eles argumentaram que o efeito é causado principalmente pela emissão de partículas soft através desses horizontes, o que eventualmente ocorrerá mesmo se o processo for assumido como adiabático. Acontece que essa decoerência está intimamente relacionada à presença de quanta de baixa frequência na radiação térmica, conforme descrita por observadores estacionários nos espaços de Schwarzschild e de Rindler, que surge dependendo da escolha do estado de vácuo. Investigamos essa afirmação em um cenário diferente, com um detector sem gap interagindo com um campo escalar massivo. Apresentamos como tal interação é descrita e como quantificar a decoerência resultante. Em seguida, analisamos nosso modelo proposto em dois casos seminais: quando os componentes da superposição espacial são inerciais e quando estão uniformemente acelerados no espaço de Minkowski. Destacamos as semelhanças e diferenças entre nossos resultados e os de estudos anteriores quando o sistema é ajustado em um regime análogo. Por fim, discutimos o que buscamos aprimorar com nosso modelo e como ele pode esclarecer algumas questões deixadas em aberto no trabalho original
Decoerência de superposição quântica em configurações relativísticas